Disposal practice and determinants of unused medicines among the general public in Gondar City, Northwest Ethiopia - Yohannes, Lamrot; Tegegne, Addisu Afrassa; Genet, Gebremariam; Workie Limenh, Liknaw; Mohammed Seid, Abdulwase; Alemayehu, Tekletsadik Tekleslassie; Ayenew, Wondim; Simegn, Wudneh (Frontiers in Public Health, 2025)
IntroductionThe inappropriate disposal of unused medicines poses significant risks to public health and the environment. Gondar City, located in Northwest Ethiopia, is not exempt from this problem. However, little is known about the current disposal practices and the determinants influencing those practices in this specific context.ObjectivesThis study aimed to evaluate the disposal practices of unused medicines among the general public in Gondar City and to identify the factors that influence these practices.MethodsA cross-sectional study design was employed to collect data from the general public in Gondar City from July 30 to August 30, 2023. Data were collected through interviews using a structured questionnaire to gather information on disposal practices and determinants that could influence disposal practices.ResultsA total of 845 respondents were involved in this study with a response rate of 93%. 56.9% of the respondents had poor disposal practices. Lower educational status [AOR = 2.76 (CI: 1.59, 4.79)]; p < 0.01, having a chronic disease [AOR = 1.79 (CI: 1.22, 2.64)]; p < 0.05, and poor knowledge toward disposal practices [AOR = 1.56 (CI: 1.12, 2.18)]; p < 0.05 were identified as significant determinants influencing poor disposal practices.ConclusionThere is an improper disposal practice of unused medicines in the study area. Lower educational status, having a chronic disease, and poor knowledge toward disposal practices were found to be significant factors. The finding underscores the need for targeted interventions to improve the safe disposal of unused medicines in Gondar City. Comprehensive educational campaigns should be launched to increase public awareness about the risks of improper disposal and promote safe disposal practices. The establishment of accessible and convenient disposal facilities or return programs should be prioritized.